PERSEPSI DAN SIKAP MASYARAKAT DALAM PEMANFAATAN TANAMAN OBAT SEBAGAI PENGOBATAN PENYAKIT SALURAN PERNAFASAN ATAS DI DESA TENGANAN PEGRINGSINGAN - Megawati, Fitria; Anita Dewi, Ni Luh Kade Arman; Agustini, Ni Putu Dewi; Suwantara, I Putu Tangkas (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Perception are obtained from inferring information in interpreting messages. Attitude is an important factor in influencing a person in making decisions in independent treatment. Medicinal plants are prevention of a disease and can be used as traditional medicine. This study aims to determine the relationship between perceptions and attitudes of the community in the use of medicinal plants as a treatment for upper respiratory tract disease. The research design used was cross-sectional. Data used was quantitative. Sampling technique is done by the method purposive sampling as many as 100 respondents. The instrument of this research is a questionnaire. Questionnaire data that has been collected is then tested using data analysis in the form of a Correlation Test Spearman. The results showed that the community perception category showed good results (54%), the attitude category showed good results (49%). The Spearman test that was carried out showed significant results with a p value of 0.007 <0.05. It can be concluded that there is a significant relationship between people's perceptions and attitudes in the use of medicinal plants as a treatment for upper respiratory tract disease